Cybersecurity Challenges in Internet Usage by Engineering Students - Solong, Ahmady; Wahid, Muliadi (Proceeding Economy of Asia International Conference, 2026)
The internet is an essential necessity among engineering students. However, to what extent do students pay attention to the issue of cybersecurity in their usage. Therefore, the objective of this study is to identify the level of cybersecurity knowledge and practices among engineering students. The study respondents were diploma engineering students at Politeknik Kuching Sarawak. The research instrument used was a questionnaire. The sampling technique used was random sampling, distributed online. Respondents answered the questionnaire based on a 5-point Likert scale provided in the questionnaire form. The analysis of this study used descriptive analysis to measure the students' level of agreement with the study items in the questionnaire based on the mean value. The results show that the level of knowledge is high, and the level of practical cybersecurity practices is good. This study is important for obtaining information on the extent to which they are aware of cybersecurity aspects, thus requiring institutional action to formulate programs that can enhance their level of awareness